Adopting Positive Selection Technology and Improving Seed Quality in Smallholder Potato Farmers in South-Western Uganda. - Kajura, Tibanyendera Deo (Kabale University, 2024)
The Potato is an important food and nutrition security as well as cash crop in Uganda, especially in the highlands where over 200,000 households who are at subsistence level depend on it for their livelihoods. Despite the importance of the crop there has been considerable reduction in yield to the current yield of 4.2 tons ha-1 by smallholder farmers which is far short of its potential on-station yields of over 25 t ha-1, mostly due to inadequate supplies of high quality seed that compels farmers to continuously use their own recycled seed with latent infections by bacterial wilt (Ralstonia solanacearum), viruses and other tuber-borne pathogens. To address this, technologies and innovations such as Positive Selection technology have been developed and promoted among smallholders to enable them generate their own clean seed on-farm for increased productivity. The main objective of the study was to assess the adoption of Positive Selection Technology and improvement of seed quality by smallholder potato farmers. Specific objectives were to: i) ascertain the adoption and use of Positive Selection by smallholders, ii) assess the extent to which Positive Selection has improved seed quality, iii) establish factors affecting farmers’ uptake of Positive Selection Technology, and iv) assess the attitudes/or perceptions of potato farmers in adopting and application of the technology. The study was conducted in two districts of Rubanda and Kabale where the technology was first popularized and promoted. A household survey was conducted with 130 respondents randomly selected. Descriptive statistics were used to analyse the data. Chi-square tests, Pearson correlation and simple regression analyses were run between different variables to assess their interactive effects on adoption of the technology. Findings of the study showed 30.0% adoption of the technology by farmers who used Positive selected seed compared to 26.9% who used certified seed. Results of the study also indicated a 12.8% and 33.1% reduction in virus and bacterial wilt disease incidences respectively with a subsequent yield increase of 112.5% attributed to use of the improved seed quality through Positive Selection technology. Pearson correlation analysis showed significant difference in yield of positive selected with unselected and certified seed (P=0.000 and 0.001 respectively). Chi-square test indicated relationship with less significant effect (p>0.05) for all demographic factor on adoption of PS technology, while all technological factors had relationship with significant effect on technology adoption. Institutional factors that had significant effect were information access, awareness and extension services. Study findings indicated that adoption of Positive Selection Technology was influenced by demographic, socio-economic, institutional and technological factors. Based on these findings, Positive Selection technology is being applied, though adoption is still low in Uganda. It is further eminently shown that the technology can improve seed quality by reduction of tuber-borne diseases with subsequent increased productivity. Demographic, socio-economic, institutional and technological factors that affect the adoption of technologies should be thought of by government and development agencies involved in designing intervention strategies focused on seed quality improvement. More farmer trainings on the technology are needed to equip farmers with knowledge and skills for effective application of the technology. Farmers should be advised to complement Positive selection with other yield enhancing technologies such as fertilizers and crop protection products and if embraced by all farmers on a large scale, it will result into increased availability of clean seed and productivity.